IITA mechanization activities and Impact - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
Mechanization expert, Engineer Diallo Thierno talks about IITA's mechanization activities and how it is impacting the cassava value chain in Africa.